Managing Households’ Expectations with Unconventional Policies - D’Acunto, Francesco; Hoang, Daniel; Weber, Michael (Review of Financial Studies, 2022)
Binding lower bounds on interest rates and large government deficits limit the scope of fiscal and monetary policies to stimulate households’ spending through financial intermediaries and firms. Policy makers have thus been implementing unconventional policies that aim to increase households’ spending directly through managing their expectations. We first show theoretically and empirically that higher inflation expectations increase households’ consumption. We then design a difference-in-differences strategy to assess the effectiveness of unconventional fiscal policy and forward guidance, both of which aim to raise aggregate demand via managing expectations. Whereas unconventional fiscal policy increases households’ expectations and spending, forward guidance announcements do not